Pengaruh Intangible, Assets, Firm Size, Investment Opportunity Set, Probitabilitas dan Coorporate Governance terhadap Firm Value pada Perusahaan Manufaktur Sektor Industri Konsumsi Periode 2014-2016 - M Rizky Fauzy; Jean Novita; Catherine Catherine; Monica Monica; Teresa Derista Maulina Girsang; Hantono Hantono; Ike , Rukmana Sari (LPPM Sekolah Tinggi Ilmu Ekonomi Al-Washliyah Sibolga, 2019)
The firm value shows that the prosperity of stakeholders will increase, if the stock price is increased as well. The value of the company becomes very important because it reflects the company's performance which can affect investors' perceptions of the company. This research is meant to find out the influence of intangible asset, firm size, invesment opportunity set, profitability and corporate governance.The research population is consumption industry companies listed on the Indonesia Stock Exchange (IDX) for the 2014-2016 periods.The sample in this study is manufacturing company according to the criteria established and there are 21 manufacturing companies and they have been selected by using purposive sampling. The statistic test instrument uses SPSS 23 version which is carried out to perform classic assumption test, multiple linear regressions analysis, and the hypothesis test. based on the result of normality test, multicolinearity test, heterocedasticity, and autocorrelation, some variables that deviate from the classic asssumption have not been found. the result of the hypothesis test shows that : (1) intangible asset is proven to affect the firm value; (2) Firm size is not proven to affect the firm value ; (3) invesment opportunity set is not proven to affect the firm value ; (4) profitability is not proven to affect the firm value ; (5) corporate governance is not proven to affect the firm value.